2022
DOI: 10.3390/microorganisms10091724
|View full text |Cite
|
Sign up to set email alerts
|

The Enzyme Gene Expression of Protein Utilization and Metabolism by Lactobacillus helveticus CICC 22171

Abstract: The purpose of this study was to explore the hydrolytic ability of Lactobacillus helveticus CICC 22171 with regard to protein and the expression of enzyme genes during protein utilization. The results revealed that the strain hydrolyzed casein from the C-terminal, reached the maximum level in 6 h, and the number of amino acids in the hydrolyzed peptide was 7–33. The molecular weight was 652.4–3432.74 kDa. Hydrophobic peptides produced by hydrolysis were the source of β-casein bitterness. Leucine and glutamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In general, many LABs contain a cell-envelope proteinase (CEP) that hydrolyzes the proteins into oligopeptides, which are further degraded into shorter peptides and amino acids by intracellular peptidases. They are taken up by the kefir microorganisms or released in the surrounding media [ 61 ]. Dallas et al [ 62 ] reported that protein fragments in milk were released in part by kefir microorganisms and in part by native milk proteases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, many LABs contain a cell-envelope proteinase (CEP) that hydrolyzes the proteins into oligopeptides, which are further degraded into shorter peptides and amino acids by intracellular peptidases. They are taken up by the kefir microorganisms or released in the surrounding media [ 61 ]. Dallas et al [ 62 ] reported that protein fragments in milk were released in part by kefir microorganisms and in part by native milk proteases.…”
Section: Discussionmentioning
confidence: 99%
“…In the experiments here, common vitamin auxotrophies were alleviated through addition of the ATCC vitamin supplement. However, in hand with amino acid auxotrophies, the abilities of an organism to scavenge amino acids into its cells vary; further, some organisms produce exopeptidases capable of breaking down complex proteins into smaller fragments, as dipeptides or free amino acids, which are then transported into the cell (Zhang et al 2022 ). Although the mucin backbone does provide a potential source of amino acids, not all bacteria produce peptidases able to cleave the mucin backbone.…”
Section: Discussionmentioning
confidence: 99%
“…Auxotrophy for amino acids in vitro can be alleviated through addition of free amino acids, peptides, or protein supplements. However, the ability of an organism to scavenge amino acids varies; only some organisms produce exopeptidases capable of breaking down complex proteins into smaller fragments, such as dipeptides or free amino acids, which are then transported into the cell (Zhang et al 2022 ). Therefore, variability in host diets leads to a difference in dietary fibers and amino acid sources consumed, ultimately conferring advantages to specific sets of microorganisms capable of breaking the discrete bond types and helping to shape the uniqueness of each microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments here, common vitamin auxotrophies were alleviated through addition of the ATCC vitamin supplement. However, in hand with amino acid auxotrophies, the abilities of an organism to scavenge amino acids into its cells vary; further, some organisms produce exopeptidases capable of breaking down complex proteins into smaller fragments, as dipeptides or free amino acids, which are then transported into the cell (Zhang et al 2022). Although the mucin backbone does provide a potential source of amino acids, not all bacteria produce peptidases able to cleave the mucin backbone.…”
Section: Discussionmentioning
confidence: 99%